Pengendalian Turnover Intention pada Pegawai Kementerian X - Setiadi, Beny Agus; Saksono, R.N. Afsdy; Asropi, Asropi (Jurnal Psikologi Teori dan Terapan, 2022)
This study aims to find the right controlling to control turnover intention in employees at Ministry X. The focus is emphasized on how the organization as a career place provides opportunities for employees to survive and advance the organization. This study uses a qualitative approach with data obtained from Ministry X participants purposely based on criteria that have made a turnover, have a turnover intention, and are staf managers. Data analysis is done by reducing, presenting, and drawing conclusions. The results of this study indicate that the turnover intention factor tends to be determined by the encouragement of internal factors. The internal factors that often arise are conveyed by participants, namely job satisfaction related to employee career clarity and employee promotion opportunities. Controls that can be carried out are by 1) Implementing internal rules regarding job information so that there is no gap between position qualifications and current employee competencies; and 2) Making policies on employee career patterns and implementing succession plans based on a merit system. Contributions in this study contribute to the control of turnover intention in government institutions. Pergerakan organisasi ditentukan oleh adanya sumber daya manusia yang memiliki peran yang besar terhadap pencapaian kinerja organisasi secara keseluruhan sehingga sumber daya manusia dalam organisasi menjadi aset yang perlu untuk dipertahankan dan perlu pengelolaan jangka panjang. Penelitian ini dilakukan untuk mengetahui faktor turnover intention dan strategi pengendalian turnover intention di Kementerian X dengan metode penelitian kualitatif. Partisipan dalam penelitian ini adalah pegawai yang bekerja di kementerian X dan pegawai yang telah melakukan turnover di kementerian X. Hasil penelitian ini menunjukan bahwa faktor turnover intention cenderung ditentukan oleh faktor internal. Faktor internal yang muncul adalah kepuasan kerja yang berhubungan dengan kejelasan karier pegawai serta peluang promosi pegawai. Strategi pengendalian yang dapat dilakukan adalah dengan adanya Penerapan kebijakan dalam pengisian jabatan, peluang promosi dan kejelasan karier